A Systematic Review of Technology-assisted Self-Management Interventions for Chronic Pain: Looking Across Treatment Modalities. Issue 6 (June 2015) - Heapy, Alicia A.; Higgins, Diana M.; Cervone, Dana; Wandner, Laura; Fenton, Brenda T.; Kerns, Robert D.
Abstract : Objectives: The use of technology to provide chronic pain self-management interventions has increased in the recent years. Individual studies have primarily focused on a single technology-assisted modality and direct comparisons of different technology-assisted modalities are rare. Thus, little is known about the relative strengths and weaknesses of each technology-assisted modality. Materials and Methods: This article is a systematic review of technology-assisted self-management interventions for chronic nonheadache, noncancer pain in adults. We examined 3 treatment modalities: telephone, interactive voice response, and Internet. Electronic searches of OVID MEDLINE, OVID PsychINFO, and the Cochrane Database of Systematic Reviews were conducted. Forty-four articles including 9890 participants were reviewed. Results: Across modalities, the existing evidence suggests that technology-assisted psychological interventions are efficacious for improving self-management of chronic pain in adults. All modalities have been shown to provide benefit and no clearly superior modality has emerged. The primary gaps in the literature are lack of in-person comparison groups, lack of direct comparison among technology-assisted modalities, and heterogeneity of methods and interventions that limit comparability across studies and modalities. Discussion: Future trials should focus on direct comparisons of technology-assisted interventions with in-person treatment and head to head comparisons of different technology-assisted modalities. Additional areas of focus include quantifying the cost of technology-assisted interventions, examining the effect of treatment "dose" on outcomes, and establishing guidelines for developing treatments for the technology-assisted environment.